Prevalence of overuse problems on World Cup alpine skiers - an explorative approach - Jahnel, R.; Spörri, J.; Kröll, J.; Müller, E. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Recurrent pain in the major joints is a common complaint among top athletes in different sports sports, particularly when involving high-loads (Jonasson et al., 2011). Acute macro trauma, repetitive micro trauma or a combination of both mechanisms may lead to overuse problems (Kujala et al., 1996). Especially structural damages, resulting from overuse at younger ages, lead to an increased risk of overuse problems under high performance training (Ogon et al., 2001). Even though, the prevalence of overuse problems has been assessed in different sports over many decades (Jonasson et al., 2011), their prevalence in competitive alpine ski racing is still unknown. Therefore, the aim of this study was, to investigate the prevalence of overuse problems at top level alpine ski racing.